(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Compound sentences are fundamental to English grammar, allowing writers and speakers to link related ideas and add variety to their language. Understanding how to construct and use compound sentences effectively is crucial for achieving fluency and sophistication in both written and spoken communication. This article will provide a detailed comparative description of English compound sentences, examining their structure, use, and variations.